Little monarchs - Case, Jonathan (Margaret Ferguson Books/Holiday House, 2022)
In the twenty-second century, a sun shift has made it impossible for mammals to survive in the daylight, and ten-year-old Elvie and her caretaker, Flora, are studying the migration route of monarch butterflies along what used to be the western coast of the United States, hoping that something in the butterflies wing scales can be used to protect people from the sun and save humanity from extinction.